A meta-analysis of the prognosis in patients with breast cancer with ipsilateral supraclavicular lymph node metastasis versus patients with stage IIIb/c or IV breast cancer - Liu, Xu-Hong (Chronic Dis Transl Med, 2016)
OBJECTIVE: To systematically evaluate the prognosis in patients with breast cancer with ipsilateral supraclavicular lymph node metastasis (SLNM) versus patients with stage IIIb/c or IV breast cancer, so as to provide evidence for clinical practice and research. METHODS: Computer retrieval from PubMed, Cochrane Libratory, CNKI (China National Knowledge Infrastructure), CBM and Wanfang Database with the assistance of other retrieval tools. All the studies evaluating the prognosis in patients with breast cancer with ipsilateral supraclavicular lymph node metastasis versus patients with stage IIIb/c or IV breast cancer were collected. Quality assessment was performed for the included data based on the quality assessment criteria appropriate for this study. Meta-analysis was performed using RevMan 5.3 software. RESULTS: A total of four references (1277 patients) were included. Assessment of influences on prognosis: As compared to the stage IIIb/c group, the 5-year survival rate was slightly lower in the SLNM group (relative risk (RR) 0.79; 95% confidence interval (CI) 0.59–1.06; Z = 1.55, P = 0.12), but there was no statistical significance; in contrast, the 5-year survival rate was significantly increased in the SLNM group as compared to the stage IV group (RR = 2.70; 95%CI: 1.36–5.37; Z = 2.84, P = 0.005). As compared to the stage IIIb/c group, the 5-year disease-free survival rate was lower in the SLNM group (RR = 0.65; 95%CI: 0.40–1.05; Z = 1.75, P = 0.08); however, there was no statistical significance. CONCLUSIONS: In patients with advanced breast cancer receiving combined therapy, the prognosis in patients with breast cancer with ipsilateral SLNM was significantly better than in those with stage IV breast cancer, and slightly worse than those with stage IIIb/c breast cancer. However, with the scarcity and poor quality of these observational studies, the long-term prognosis remains to be further verified in large-sample, high-quality studies.